K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

15 tháng 9 2020

\(x^2+4x\) 

\(=x\left(x+4\right)\) 

\(x^2-16\) 

\(=x^2-4^2\) 

\(=\left(x-4\right)\left(x+4\right)\)

15 tháng 9 2020

1) x2 + 4x

= x(x + 4)

2) x2 - 16

= x2 - 42

= (x - 4)(x + 4)

Linz

15 tháng 9 2020

1. x2 - 2x - 3

= x2 + x - 3x - 3

= x( x + 1 ) - 3( x + 1 )

= ( x + 1 )( x - 3 )

2. x2 - 4x + 3

= x2 - x - 3x + 3

= x( x - 1 ) - 3( x - 1 )

= ( x - 1 )( x - 3 )

15 tháng 9 2020

\(x^2-2x-3\) 

\(=x^2-3x+x-3\) 

\(=x\left(x-3\right)+1\left(x-3\right)\) 

\(=\left(x-3\right)\left(x+1\right)\) 

\(x^2-4x+3\) 

\(=x^2-3x-x+3\) 

\(=x\left(x-3\right)-1\left(x-3\right)\) 

\(=\left(x-3\right)\left(x-1\right)\)

1 tháng 10 2016

1/ x² - 5x + 6 = 0 
⇔ x² - 2x - 3x + 6 = 0 
⇔ x(x - 2) - 3(x - 2) = 0 
⇔ (x - 2)(x - 3) = 0 
⇒S = {2 ; 3}.

1 tháng 10 2016

1) \(x^2+5x+6=0\)

\(\Leftrightarrow x^2+2x+3x+6=0\)

\(\Leftrightarrow x\left(x+2\right)+3\left(x+2\right)=0\)

\(\Leftrightarrow\left(x+2\right)\left(x+3\right)=0\)

\(\Leftrightarrow\left[\begin{array}{nghiempt}x+2=0\\x+3=0\end{array}\right.\)\(\Leftrightarrow\left[\begin{array}{nghiempt}x=-2\\x=-3\end{array}\right.\)

2) \(2\left(x+3\right)-x^2-3x=0\)

\(\Leftrightarrow2\left(x+3\right)-x\left(x+3\right)=0\)

\(\Leftrightarrow\left(x+3\right)\left(2-x\right)=0\)

\(\Leftrightarrow\left[\begin{array}{nghiempt}x+3=0\\2-x=0\end{array}\right.\)\(\Leftrightarrow\left[\begin{array}{nghiempt}x=-3\\x=2\end{array}\right.\)

3) \(x^2+4x+3=0\)

\(\Leftrightarrow x^2+x+3x+3=0\)

\(\Leftrightarrow x\left(x+1\right)+3\left(x+1\right)=0\)

\(\Leftrightarrow\left(x+1\right)\left(x+3\right)=0\)

\(\Leftrightarrow\left[\begin{array}{nghiempt}x+1=0\\x+3=0\end{array}\right.\)\(\Leftrightarrow\left[\begin{array}{nghiempt}x=-1\\x=-3\end{array}\right.\)

4) \(2x^2-3x-5=0\)

\(\Leftrightarrow2x^2+2x-5x-5=0\)

\(\Leftrightarrow2x\left(x+1\right)-5\left(x+1\right)=0\)

\(\Leftrightarrow\left(x+1\right)\left(2x-5\right)=0\)

\(\Leftrightarrow\left[\begin{array}{nghiempt}x+1=0\\2x-5=0\end{array}\right.\)\(\Leftrightarrow\left[\begin{array}{nghiempt}x=-1\\x=\frac{5}{2}\end{array}\right.\)

23 tháng 6 2019

\(1,\)\(3x-3y-x^2+2xy-y^2\)

\(=-\left(x^2-2xy+y^2\right)+\left(3x-3y\right)\)

\(=-\left(x-y\right)^2+3\left(x-y\right)\)

\(=\left(x-y\right)\left[-\left(x-y\right)+3\right]\)

\(=\left(x-y\right)\left(3-x+y\right)\)

\(2,\)\(49\left(x-4\right)^2-9\left(x+2\right)^2\)

\(=\left[7\left(x-4\right)\right]^2-\left[3\left(x-2\right)\right]^2\)

\(=\left(7x-28-3x+6\right)\left(7x-28+3x-6\right)\)

\(=\left(4x-22\right)\left(10x+34\right)\)

\(3,\)\(x^4+4x^2-5\)

\(=x^4-x^2+5x^2-5\)

\(=x^2\left(x^2-1\right)+5\left(x^2-1\right)\)

\(=\left(x^2+5\right)\left(x-1\right)\left(x+1\right)\)

23 tháng 10 2016

A = x(x + y)2 - x(x - y)

= x[(x + y)2 - (x - y)]

B = (2x - 3)(4x2 + 6x + 9) - (2x + 3)(4x2 - 6x + 9)

= 8x3 - 27 - 8x3 - 27

= - 54

C = (x + 3)3 - (x - 3)3 - 18x2 - 18

= x3 + 9x2 + 27x + 27 - x3 + 9x2 - 27x + 27 - 18x2 - 18

= 36

17 tháng 2 2020

\(\frac{x-23}{24}+\frac{x-23}{25}=\frac{x-23}{26}\)

\(\Leftrightarrow\frac{x-23}{24}+\frac{x-23}{25}-\frac{x-23}{26}=0\)

\(\Leftrightarrow\left(x-23\right)\left(\frac{1}{24}+\frac{1}{25}-\frac{1}{26}\right)=0\)

\(\Leftrightarrow x-23=0\left(vì\frac{1}{24}+\frac{1}{25}-\frac{1}{26}\ne0\right)\)

\(\Leftrightarrow x=23\)

vậy................

\(\frac{201-x}{99}+\frac{203-x}{97}+\frac{205-x}{95}+3=0\)

\(\Leftrightarrow\left(\frac{201-x}{99}+1\right)+\left(\frac{203-x}{97}+1\right)+\left(\frac{205-x}{95}+1\right)=0\)

\(\Leftrightarrow\frac{300-x}{99}+\frac{300-x}{97}+\frac{300-x}{95}=0\)

\(\Leftrightarrow\left(300-x\right)\left(\frac{1}{99}+\frac{1}{97}+\frac{1}{95}\right)=0\)

\(\Leftrightarrow300-x=0\left(vì\frac{1}{99}+\frac{1}{97}+\frac{1}{95}>0\right)\)

\(\Leftrightarrow x=300\)

vậy..........